Racing to the Bottom or to the Top? Decentralization, Revenue Pressures, and Governance Reform in China. (July 2017) - van der Kamp, Denise; Lorentzen, Peter; Mattingly, Daniel
Highlights: Some say fiscal transfers help central authorities control budget-poor localities. Evidence from transparency reforms in China suggests the opposite. Cities with weak revenue streams are less likely to implement transparency reforms. Foreign investment and pollution increase transparency in fiscally strong cities. Fiscally weak cities aim behave like pollution havens, blocking transparency. Summary: China's decentralization has been praised for promoting inter-jurisdictional competition that incentivizes local officials to promote economic development. The downside of decentralization is that it enables these same local authorities to slow or block implementation of centrally mandated governance reforms, especially when these may negatively affect local development goals. We suggest that China's fiscal system and promotion system have created mismatched incentives that encourage cash-strapped local authorities to disregard central governance reforms. Specifically, we show that cities with weaker revenue bases were slower to implement new, centrally mandated environmental transparency regulations. Additional evidence points to a bifurcation in development strategies. In fiscally strong cities, increased foreign investment leads to greater compliance. In fiscally weak cities, foreign investment is associated with decreased disclosure, suggesting they aim to promote local development by becoming pollution havens. Similarly, high levels of pollution induce fiscally strong cities to increase pollution disclosures while the opposite holds in fiscally weak cities. These findings imply that mismatched decentralization policies can undermine other important governance reforms, even ones that might be expected to be complementary to decentralizing initiatives.